Keabsahan pembacaan akta melalui video conference di era digitalisasi - Fasya, Gania (Cessie : Jurnal Ilmiah Hukum, 2022)
This study aims to analyze the reading and signing of the deed via video conference, it is related to the concept of cyber notary. In this era of globalization, where there are openings and opportunities to conduct transactions carried out electronically, especially in electronic certification carried out by a notary. This journal was created to examine the authority of a notary in certifying transactions carried out electronically related to the reading and making of the deed via video conference. The research method used in writing this journal is an empirical legal research method or sociological juridical, namely using a statutory, case, and historical approach. In this case the author draws a conclusion that with regard to electronic certification, if it is associated with reading and signing the deed carried out by a notary through video conference, it cannot be implemented by a notary, this is because there are no definite regulations governing and several conflicting regulations related to certification. transactions conducted electronically include the Civil Code and Article 1 number 7 of the Law on Notary Positions. Based on the results of this study, the authority of a notary related to electronic certification related to reading and reading words through video conference cannot be applied because there are no definite regulations governing it, the implementation of this electronic certification must be synchronized between regulations so that there are no conflicting regulations so that the implementation of this electronic certification has clear regulations and certainly legal certainty for notaries and other parties.